1997
DOI: 10.1093/ndt/12.12.2542
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural background of albuminuria in rats with passive Heymann nephritis

Abstract: Depletion of serum complement decreases subepithelial EDDs as well as the number of sites with decreased anionic charge underlying the EDDs. Thus, the size of subepithelial EDDs plays a pivotal role in the onset of albuminuria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…This indicates that the permeability of the GBM itself was already enhanced in these rats and implies that subepithelial deposit formation per se, with or without complement activation, can perturb the integrity of the glomerular permselective filter in the GBM. The observed reduction in the glomerular anionic sites in the LRE in PHN, with or without complement depletion, supports this suggestion, as proposed in an earlier report [4]. However, as seen in PHN-CVF-rats, the reduction in glomerular anionic sites in itself was not sufficient to lead to significant proteinuria.…”
Section: Discussionsupporting
confidence: 88%
“…This indicates that the permeability of the GBM itself was already enhanced in these rats and implies that subepithelial deposit formation per se, with or without complement activation, can perturb the integrity of the glomerular permselective filter in the GBM. The observed reduction in the glomerular anionic sites in the LRE in PHN, with or without complement depletion, supports this suggestion, as proposed in an earlier report [4]. However, as seen in PHN-CVF-rats, the reduction in glomerular anionic sites in itself was not sufficient to lead to significant proteinuria.…”
Section: Discussionsupporting
confidence: 88%
“…The deposition of Ab at the base of the GEC and the in situ formation of immune complexes in the GBM has been shown to cause charge and hemodynamic effects capable of causing proteinuria (49). The structural effect on the GBM of enlarging sub-GEC deposits may cause proteinuria (9,50,51). The mechanical effects of these sub-GEC deposits such as retraction of GEC and reduced density of anionic sites in the lamina rara externa may be critical to the development of proteinuria (50).…”
Section: Pvg/c6mentioning
confidence: 99%
“…The structural effect on the GBM of enlarging sub-GEC deposits may cause proteinuria (9,50,51). The mechanical effects of these sub-GEC deposits such as retraction of GEC and reduced density of anionic sites in the lamina rara externa may be critical to the development of proteinuria (50). A number of other local mediators have been postulated to damage GBM and GEC, such as reactive oxygen species (52) and PGs (53).…”
Section: Pvg/c6mentioning
confidence: 99%
“…It is well known that treatment with cobra venom factor (CVF), which depletes serum complement, prevents development of proteinuria in PHN. Arai et al [22] demonstrated decreased size of subepithelial deposits and reduced retraction of glomerular epithelial cells in CVFtreated animals in the heterologous phase of PHN. Although the proteinuria was prevented, the density of anionic sites in the GBM, estimated by ruthenium red (RR), was not significantly different in the PHN with or without CVF treatment.…”
Section: Discussionmentioning
confidence: 96%
“…Loss of glomerular anionic sites has been documented in PHN using various cationic probes [1,[21][22][23] . In the study by Arai et al [21] , anionic charge of the GBM in the heterologous phase of PHN was examined by measurements of ruthenium red binding to the GBM.…”
Section: Discussionmentioning
confidence: 99%